A CONCEPÇÃO DE ÉTICA NO PENSAMENTO DE KIERKEGAARD - COSTA, Thondason Dhonas de Jesus (2023)
The conception of ethics in Kierkegaard's thought has an approach focused on the individual by penetrating their interiority, basing their faith on singularity. The human being, the moment he sees the set of possibilities, begins to reflect on his relationship with the world, with himself and with God. It is in the freedom to choose, in the face of different possibilities, that the individual consolidates his existential singularity. Kierkegaard's philosophical anthropology proposes a human existence based on the complexity between the soul and the body and surpassed by the spirit, that is, making it take a specific way of living its existence through human, religious and social relationships, which differs of the animals. When analyzing Kierkegaard's works, we find that the philosopher's objective is not to generalize the human being, but to respect singularity. The human being is equally in relationship with himself, using existential possibilities to find a “self”. When the individual finds it difficult to maintain this relationship with himself and with God, it consequently leads him to despair. The despair that the philosopher presents in the book The Works of Love is the same that human beings feel when they experience the death of their self, the desperate person lives without finding the true meaning of life, he wants to be a self that he is not really. In Christian ethics, the ethical does not deny subjectivity, because to love “neighbors”, it is necessary to affirm subjectivity, individuality, it is necessary to love oneself.